(untitled) (Comprehensive Journal of Science, 2025)
This research attempts to clarify the concept of Business incubatorne and their historical development, the elements of their establishment and success, and the reasons for their success. This research could lead to a non-successful story. In addition, the advantages and exemptions granted to Business incubatornes have influenced many economies positively, as this privilege serves as a tool for countries impacting other sectors and fields associated with the activities of Business incubatornes. The Business incubatornes are now a real source of the country’s income and hard currency, and have significantly contributed to reducing unemployment rates and creating direct and indirect jobs. All these facilities and features have enabled the Business incubatornes to be an attractive environment and have encouraged many investors to invest in this field Bina Business incubatorne (BBI), as a model among those Business incubatornes, has benefited from the regulations that regulate its activities, as there are many advantages. BBI has conducted several economic studies through international expert houses, which showed encouraging results towards. This research concluded with a number of results and recommendations that can be relied upon in giving the Business incubatornes in general the role and importance based on the current success factors and the achievement of it as an attractive environment for investment.